A rare cause of hepatomegaly in the childhood: Lysosomal acid lipase deficiency - Pınar Haznedar; Zarife Kuloğlu; Aydan Kansu; F. Tuba Eminoğlu (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Haznedar P, Kuloğlu Z, Kansu A, Eminoğlu FT. A rare cause of hepatomegaly in the childhood: Lysosomal acid lipase deficiency. Turk J Gastroenterol 2018; 29: 518-9.